Aquatic birnavirus induces apoptosis through activated caspase-8 and -3 in a zebrafish cell line - Hong, J-R (Journal of fish diseases, 2005)
In this study, the possible influence of temperature on infectious pancreatic necrosis virus (IPNV)-induced apoptosis in a zebrafish liver epithelium (ZLE) cell line was investigated. At a lower temperature (18 degrees C), there was expression of viral proteins VP2 and VP3 at 4 h post-infection (p.i.). At this time no expression was found in the high temperature group at 28 degrees C. The cell survival ratio was 52 and 18% at 24 and 48 h p.i., respectively, during IPNV infection at 18 degrees C. In addition, we assayed for apoptosis in IPNV-infected cells with terminal deoxynucleotidyl transferase (TdT)-mediated end labelling (TUNEL) of DNA at different dosages of virus. We found a ratio of apoptotic cells of 8 and 25% at 12 and 18 h p.i., respectively, in the multiplicity of infection (MOI) 1 group. The MOI 10 group had 20 and 45% apoptotic cells at 12 and 18 h, respectively. Furthermore, at 18 degrees C IPNV activated the caspase-8 and 3 from 1.5 to 2 times at 12 and 18 h p.i., respectively. Taken together, these findings suggest that successful virus replication occurs at the low temperature (18 degrees C) compared with the non-permissive temperature of 28 degrees C. Thus, IPNV replication is capable of activating caspase-8 and -3 and inducing host apoptosis